The Representation of Mystical Elements in the Character of Teungku Don in the Novel Percikan Darah di Bunga by Arafat Nur: A Mimetic and Expressive Perspective - Nurrahmah, Nurrahmah; Wulanda, Wulanda; Furqan, Al (Universitas Nusantara PGRI Kediri, 2025)
This study examines mystical elements in Teungku Don’s character in Arafat Nur’s novel Percikan Darah di Bunga, exploring their interplay with Acehnese spirituality, social conflict, and cultural identity. Employing a descriptive qualitative design with mimetic and expressive approaches, primary data were drawn from the novel’s text and supplemented by relevant secondary sources. Data were collected through literature review and document analysis, then analyzed using Miles and Huberman’s three-stage model (data reduction, data presentation, and conclusion drawing). Findings reveal seven dimensions of mystical representation: (1) an innate spiritual aura; (2) dhikr practices enabling transcendental experiences and soul release; (3) perception of supernatural phenomena; (4) telepathic insight into others’ thoughts and feelings; (5) prophetic visions through dreams; (6) eccentric behavior as a social marker of mysticism; and (7) the limits of mystical power in shaping conflict outcomes. These dimensions not only reflect entrenched spiritual traditions within Acehnese society but also serve as a literary vehicle to probe themes of social tension, identity formation, and the search for meaning amid violence. The study contributes to literary and cultural scholarship by demonstrating how mystical motifs articulate and negotiate socio-cultural dynamics in Aceh.